Evaluación de la vulnerabilidad del acuífero de Santa María. Informe preliminar - Ballesteros, Idania; Caballero, Alberto; Bayard, Carmelo; Villareal, José; Leone, Orlando; Jaén, Janira; Miranda, Mario Luis; Tapia, Arkin; Manzané, Mirna; Cedeño, Iván; Sánchez, Sebastián (Visión Antataura, 2018)
.